2016
DOI: 10.2147/copd.s84347
|View full text |Cite
|
Sign up to set email alerts
|

Depression, body mass index, and chronic obstructive pulmonary disease – a holistic approach

Abstract: BackgroundSeveral clinical studies suggest common underlying pathogenetic mechanisms of COPD and depressive/anxiety disorders. We aim to evaluate psychopathological and physical effects of aerobic exercise, proposed in the context of pulmonary rehabilitation, in a sample of COPD patients, through the correlation of some psychopathological variables and physical/pneumological parameters.MethodsFifty-two consecutive subjects were enrolled. At baseline, the sample was divided into two subgroups consisting of 38 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
6
1
Order By: Relevance
“…Our findings are consistent with others who reported that elderly patients (whose mean age is 71 years) achieved a clinically significant reduction in depression following rehabilitation 30,31. Moreover, our findings are consistent with studies that concluded that patients over 71 attained similar alleviation from depression, but also that elderly patients should not be excluded from pulmonary rehabilitation 20.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with others who reported that elderly patients (whose mean age is 71 years) achieved a clinically significant reduction in depression following rehabilitation 30,31. Moreover, our findings are consistent with studies that concluded that patients over 71 attained similar alleviation from depression, but also that elderly patients should not be excluded from pulmonary rehabilitation 20.…”
Section: Discussionsupporting
confidence: 93%
“…Characterizing disturbance of mood by the Impacts component score of the SGRQ may also be viewed as a possible shortcoming. Identification of depression based on the Diagnostic and Statistical Manual of Mental Disorders 5 may prove to be challenging as accompanying somatic symptoms could be secondary to either depression or COPD 43. Furthermore, utility of certain diagnostic instruments, for example, hospital anxiety and depression scale, has been questioned with respect to their accuracy in COPD patients 59.…”
Section: Discussionmentioning
confidence: 99%
“…In puberty, significant changes in body composition occur and need to be taken into account for the longitudinal examination of youth with BSD ( 48 ). A positive association between fat mass and depressive symptoms exists ( 98 , 99 ). Among many pathways, depressive symptoms may cause lipid dysregulation resulting in increased fat accumulation ( 82 ).…”
Section: Body Composition and Mood Disordersmentioning
confidence: 99%